Perubahan Batasan Umur Pernikahan dalam Perspektif Maqashid Syariah - Haikal Fakhri, Muhammad; Khasanah, Fitrohtul; Marzuki, Arifuat (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Underage marriage is still a big legal and social problem in Indonesia. In the perspective of Islamic family law, marriage validity depends on fulfilling the legal pillars and conditions without a strict age limit, Law No. 16 of 2019 says that the bride and groom must be at least 19 years old. This study seeks to examine Islamic family law and safeguarding children viewpoints about underage marriage and to delineate their areas of convergence. Using descriptive-comparative analysis of main and secondary legal texts, the study takes a normative-juridical approach. The findings show that while Islamic law does not specifically restrict marriage age, the maqasid syariah prioritizes the protection of life and lineage (hifz an-nafs and hifz an-nasl), which is consistent with national law's best interests of the kid premise. Therefore, within the contemporary framework of child protection, the age restriction in marriage is an embodiment of sharia values.